Photodynamic Therapy Using IR-783 Liposomes for Advanced Tongue and Breast Cancers in Humans - Yasuo Komura; Shintarou Kimura; Yumi Hirasawa; Tomoko Katagiri; Ayana Takaura; Fumika Yoshida; Saki Fukuro; Hiromi Muranishi; Osamu Imataki; Koichiro Homma (Journal of Functional Biomaterials)
Photodynamic therapy (PDT) is a minimally invasive treatment that elicits tumor apoptosis using laser light exclusively applied to the tumor site. IR-783, a heptamethine cyanine (HMC) dye, impedes the proliferation of breast cancer cells, even without light. Although studies have investigated the efficacy of IR-783 in cell and animal studies, its efficacy in clinical settings remains unknown. Therefore, we aimed to determine the efficacy of PDT using IR-783 liposomes. An HMC dye, excited by long-wavelength infrared light and with high tissue permeability, was used for PDT after liposomization to enhance tumor tissue accumulation. PDT was performed using IR-783 in two patients with either tongue or breast cancer, one each. IR-783 liposomes inhibited cell proliferation in tongue cancer cells even when not excited by light. Tumor size was markedly reduced in both cases, with no significant adverse events. Furthermore, the patient with tongue cancer exhibited improved respiratory, swallowing, and speech functions, which were attributed not only to the shrinkage of the tumor but also to the improvement in airway narrowing. In conclusion, PDT using IR-783 liposomes effectively reduces tumor size in tongue and breast cancers.